Relationship between Asphyxia History in Newborn with the Development of Infants Aged 3-12 Months - Kusparlina, Eny Pemilu; Hardika, Mufida Dian (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2017)
Development is the increasing ability or skill in the structure and function of the body more complex in a regular pattern and can be predicted as a result of maturation. The development is begun since in the womb until  adulthood is prenatal period, infancy, and childhood, are followed by pre-adolescence, early adolescence, and late adolescence. One of the factors that influence the development of an infant or child is a childbirth factor  in which the newborn infant has asphyxia. If the infant has asphyxia, especially in severe asphyxia that has a value of 0-3 APGAR can affect the infants development in next life because it is associated with nerve damage due to lack of oxygen during birth process.This research had purposes to identify the relationship between asphyxia history in newborn and the development of infants aged 3-12 months. This research used retrospective design, by involving 100 infants aged 3-12 months which were taken by simple random sampling. Data collection was done by examining of infant development by using KPSP instrument checklist based on infant age and then the researcher searches the history of APGAR Score of (occurence of asphyxia) when the infant was born in the midwifes medical records that helped childbirth. The result of Chi Square test = 0.021 (<0.05), so it could be concluded that there was a significant relationship between the history of asphyxia in newborns and the development of infants aged 3-12 months.